Creative Brand Publicity (CBP): The Power of Mood, Moment, and Movement - Bambang Sukma Wijaya (Jobmark: Journal of Branding and Marketing Communication, 2020)
This conceptual paper introduces Creative Brand Publicity (CBP) as a narrative strategy that emphasizes emotional depth, contextual relevance, and dynamic continuity in brand communication. Brands face growing challenges in capturing attention and sustaining meaningful audience engagement. These challenges emerge, especially in an increasingly saturated and algorithm-driven media environment. Traditional publicity approaches often prioritize exposure over resonance, creating a gap between visibility and narrative impact. The study aims to develop and elaborate a conceptual framework of CBP structured around three fundamental aspects: Mood, Moment, and Movement. Adopting a conceptual and theory-building approach, this paper synthesizes insights from branding, marketing communication, narrative theory, and cultural studies. The analysis integrates existing literature with interpretive reasoning to construct a cohesive framework that explains how brands can design more engaging and meaningful publicity strategies. The paper proposes that effective brand publicity operates through the orchestration of Mood as the emotional tone shaping audience perception, Moment as the contextual and temporal relevance enhancing immediacy and connection, and Movement as the continuity and evolution of brand narratives across platforms and touchpoints. These three aspects work together to turn publicity from simple information sharing into engaging stories that people remember and connect with. Theoretically, this study contributes to branding and marketing communication literature by advancing a narrative-based model of publicity that extends beyond conventional promotional frameworks. It offers practical guidance to practitioners on designing integrated, adaptive, culturally resonant publicity initiatives in the digital era. The CBP framework provides a foundation for future empirical research and the development of more human-centered and story-driven brand communication strategies.